EFFICIENCY OF USING SOME POLYCOMPONENT MATHEMATICAL MODELS OF SELECTION INDICES FOR EVALUATION OF YOUNG PIGS FOR FATTENING AND MEAT QUALITIES - Khalak, V.; Gutyj, B.; Il’chenko, M.; Shostya, A.; Usenko, S.; Petulko, P. (Scientific Progress & Innovations, 2022)
The paper presents the results of studies of some fattening and meat qualities of young pigs of different interbreeding differentiation according to some multicomponent mathematical models and calculates the correlations between traits and economic efficiency of research results. The research was conducted in agricultural formations of the Dnipropetrovsk region, the “Jazz” meat-packing plant, and the livestock laboratory of the State Institution Institute of Grain Crops of NAAS. The work was performed according to the research program of NAAS No. 30, “Innovative technologies of breeding, industrial and organic production of pig products (“Pig”). Evaluation of young pigs of large white breed for fattening and meat qualities was carried out taking into account the following indicators: the average daily increase in live weight during the period of control fattening, g; the age of achievement of live weight of 100 kg, days; fat thickness at the level of 6–7 thoracic vertebrae, mm; length of the chilled carcass, cm; length of bacon half of chilled half-carcass, cm. Control fattening of young pigs was carried out on the farm according to M. D. Berezovsky, I. V. Khatko (2005) method. The cost of additional products was calculated according to the “Methods for determining economic efficiency…” (1983), biometric indicators – according to Kovalenko V. P., etc. (2010). It was found that young pigs of the controlled population at the age of 100 kg, fat thickness at the level of 6–7 thoracic vertebrae, and the length of the chilled carcass correspond to the elite class. Young pigs of the I experimental group of interbreeding differentiation on the indices “Iв”, “I”, and “И” on average outperformed peers of III and II groups at the age of 100 kg by 4.07, the thickness of the fat at the level of 6–7 thoracic vertebrae – 13.57 and the length of chilled carcasses – 1.22 %. There was no significant difference between the groups in the length of the bacon half of the chilled carcass. The criteria for selection of highly productive animals according to the indices “Iв”, “I” and “И” are indicators 214.89–242.85, 585.67–8337.69, and 0.054–1.164 points, respectively. The significant correlations between young white pigs’ breeding indices, fattening, and meat qualities are 53.33 %. This indicates the effectiveness of the use of these indices in breeding work. The maximum increase in additional products was obtained from young animals of the I experimental group of interbreeding differentiation according to the index “Iв” (+3.98 %), “I” (+4.40 %), and “И” (+1.27 %).